Pengaruh MBKM Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa - Yayuk Setyawati; Firsta Bagus Sugiharto; Rofik Jalal Rosyanafi; Bagus Cahyanto; Titis Angga Rini; Ali Yusuf (MOTORIC, 2021)
The purpose of this study is to awaken students' interest in entrepreneurship through entrepreneurship based entrepreneurship education MBKM. This type of study is quasi experimental and focuses on students enrolled in entrepreneurship courses. The results demonstrate that MBKM based entrepreneurship education can stimulate students' interest in entrepreneurship. Students will find it beneficial to develop an understanding of caring for others and their environment, reaching their potential and caring for them in a spirit of collaboration and mutual cooperation. Keywords : Interest in Entrepreneurship, Entrepreneurship Education, Entrepreneurship MBKM.